1-Ferrocenyl-3-(2-methylanilino)propan-1-one - Leka, Zorica (International Union of Crystallography, 2012)
In the ferrocene-containing Mannich base, [Fe(C(5)H(5))(C(15)H(16)NO)], the dihedral angle between the mean planes of the benzene ring and the substituted cyclopentadienyl ring is 84.63 (7)°. The conformation of the title compound significantly differs from those found in corresponding m-tolylamino and p-tolylamino derivatives. In the crystal, C—H⋯O interactions connect the molecules into chains, which further interact by means of C—H⋯π interactions. It is noteworthy that the amino H atom is shielded and is not involved in hydrogen bonding.